Safety at work and immigration - Cristina Bellés-Obrero; Nicolau Martin Bassols; Judit Vall Castello (Journal of Population Economics, 2020)
This paper examines the effect of immigration on workplace safety, an understudied outcome in the literature. We use a novel administrative dataset of the universe of workplace accidents reported in Spain from 2003 to 2015 and follow an instrumental variables (IV) strategy based on the distribution of early migrants across provinces. Our results show that the massive inflow of immigrants between 2003 and 2009 reduced the number of workplace accidents by 10,980 for native workers (7% of the overall reduction during that period). This decline in workplace accidents is driven by Spanish-born workers shifting away from manual occupations to occupations involving more interpersonal interactions. Immigrant flows during the economic crisis (2010–2015) had no impact on natives' workplace safety. The scarcity of jobs during that period may have prevented shifts between occupations. Finally, we find no effects of immigration on the workplace safety of immigrants. These results add a previously unexplored dimension to the immigration debate that should be taken into account when evaluating the costs and benefits of migration flows.
Keywords: J61; J28; I1; 330; Immigration; Workplace accidents; Safety at work